Respiration and sleep in Parkinson's disease. Issue 12 (December 1985) - Apps, M C; Sheaff, P C; Ingram, D A; Kennard, C; Empey, D W
Abstract : Sleep and respiration during sleep were studied in patients with idiopathic Parkinson's disease, patients with Parkinsonism with autonomic disturbance, and normal age and sex matched controls. Patients with idiopathic Parkinson's disease showed significantly reduced REM sleep, and more frequent and prolonged waking throughout the night. Hypoventilation and sleep apnoea did not occur in the idiopathic Parkinson's disease or normal groups, but respiration was disorganised with frequent central and obstructive apnoeas in the autonomic disturbance group. Respiratory rate during non rapid eye movement sleep was similar in the idiopathic Parkinson's disease and normal groups, but patients with idiopathic Parkinson's disease showed tachypnoea awake and during REM sleep.